2017
DOI: 10.1038/srep43841
|View full text |Cite
|
Sign up to set email alerts
|

Intact sensory-motor network structure and function in far from onset premanifest Huntington’s disease

Abstract: Structural and functional changes attributable to the neurodegenerative process in Huntington’s disease (HD) may be evident in HTT CAG repeat expansion carriers before the clinical manifestations of HD. It remains unclear, though, how far from motor onset a consistent signature of the neurodegenerative process in HD can be detected. Twelve far from onset preHD and 22 age-matched healthy control participants underwent volumetric structural magnetic resonance imaging (MRI), diffusion tensor imaging (DTI), and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…A third independent study reported decreased connectivity in thalamus and temporal gyrus of subcortical network, whereas increased connectivity was observed within the frontal gyrus (Wolf, Sambataro, Vasic, Depping, et al, ). In pre‐HD, two independent studies, implementing a seed‐based connectivity approach, failed to report network changes (Gorges et al, ; Seibert et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…A third independent study reported decreased connectivity in thalamus and temporal gyrus of subcortical network, whereas increased connectivity was observed within the frontal gyrus (Wolf, Sambataro, Vasic, Depping, et al, ). In pre‐HD, two independent studies, implementing a seed‐based connectivity approach, failed to report network changes (Gorges et al, ; Seibert et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Classification based on presence or absence of mutated HTT gene is ideal to study within-subject reliability: genetic labels have virtually no associated noise, and are strictly stable across visits. Moreover, because functional differences are mild in gene-carriers far from symptom onset 21 , the sensitivity to test-retest fluctuations is expected to be higher than for strong neurological signatures. We trained binary classifiers using sex-and age-corrected FCD maps validated using LOSO-CV to ensure robustness to site differences.…”
Section: Scientific Reports |mentioning
confidence: 99%
“…Images are accompanied by a wealth of cognitive and motor measures, most also acquired during preceding TRACK-HD visits, in combination spanning up to 7 yearly measurements. Such a rich dataset allows for the estimation of subtle longitudinal changes in cognition and motor control, allowing subjects to be compared to their own performance baselines, and enabling analyses of population heterogeneity for a stage at which systematic brain differences from controls are mild 21 . In addition, because performance on different tasks might rely on the same affected neural systems, it is possible to identify combinations of measures for which longitudinal changes covary, potentially boosting behavioural signal-to-noise and isolating common brain structures responsible for cognitive decline.…”
mentioning
confidence: 99%
“…And which diseased brain regions are suspect to be associated with a particular pattern of eye movement disturbances? These questions cannot be fully addressed yet, but systematic studies investigating eye movement control and brain connectivity ( 75 , 76 ) may indicate that network-based functional connectivity alterations are associated with worsened executive oculomotor function and that functional abnormalities may precede microstructural and macrostructural changes. Although the primary visual cortex in PD appears to be spared by the pathological process ( 60 ), a broad spectrum of visuo-oculomotor dysfunctions including color vision ( 77 ) and diplopia have been reported ( 78 ).…”
Section: Brain Network and Oculomotor Disturbances In Parkinsonian Smentioning
confidence: 99%